2019
DOI: 10.29333/iji.2019.12164a
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Iranian English High School Teachers’ Reflective Practices, Their Self-Regulation and Teaching Experience

Abstract: The study examined the relationship between English teachers' reflective practices and their self-regulation. It also explored the relationships between self-regulation and teachers' teaching experiences. To achieve the goal of the study, 103 English teachers from different senior and junior high schools were selected through convenience sampling based on availability and based on their consent to participate in the study. They were asked to complete two questionnaires: the English Language Teaching Reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
18
1
1
Order By: Relevance
“…Therefore, it needs further investigation. However, this research result is partially congruent with that of Ghansoli and Ghanizadeh (2013) which says there is no relationship between teachers self-regulation and gender; but a positive significant relationship with teaching experience; Pazhoman and Sarkhosh (2019) no relationship between self-regulation and teachers' teaching experience; Partovi and Tafalozi (2016) no relationship between gender and self-regulated teaching, but positive relationship with teaching experience. Some of the findings of the study conducted by Liu et al (2011)in Handan indicated that the status of self-regulated learning behavior of chemistry teachers is the same between male and female teachers, across all school levels but different among teachers' experience, which says young teachers' self-regulated learning behavior better than old teachers which is contrary to Partovi and Tafazolis' (2016), and (Chao and Chou, 2017) studys' result.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, it needs further investigation. However, this research result is partially congruent with that of Ghansoli and Ghanizadeh (2013) which says there is no relationship between teachers self-regulation and gender; but a positive significant relationship with teaching experience; Pazhoman and Sarkhosh (2019) no relationship between self-regulation and teachers' teaching experience; Partovi and Tafalozi (2016) no relationship between gender and self-regulated teaching, but positive relationship with teaching experience. Some of the findings of the study conducted by Liu et al (2011)in Handan indicated that the status of self-regulated learning behavior of chemistry teachers is the same between male and female teachers, across all school levels but different among teachers' experience, which says young teachers' self-regulated learning behavior better than old teachers which is contrary to Partovi and Tafazolis' (2016), and (Chao and Chou, 2017) studys' result.…”
Section: Discussionsupporting
confidence: 83%
“…In opposition to the above studies, Partovi and Tafazoli (2016) reported a positive relationship between the teachers' reflective practices and their self-regulation but no significant relationships between teachers' self-regulation and their experiences. In addition to Pazhoman and Sarkhosh (2019) , Arrastia (2015) identified that there was no correlation between teachers' teaching experience, their qualification, and the grade level they teach with their self-regulation in Caslers' (2005) unpublished validating study. And in this study, the relationship between teachers' teaching experience and their self-regulation practice was also identified.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assessment was found to have no significant relationship with reflective thinking. This contradicts the findings of several studies (i.e., Choy et al, 2017;Pazhoman & Sarkhosh, 2019;Pfitzner-Eden, 2016) that showed that self-assessment is positively correlated with reflective thinking, and indicates that female elementary teachers do not use the feedback from their students and colleagues to improve their teaching. This shows that there is a need to design reflective thinking experiences and contexts for Saudi female teachers to develop their reflection skills.…”
Section: Discussioncontrasting
confidence: 67%
“…They also concluded that EFL teacher self-efficacy had no significant impact on the relationship between self-regulation and locus of control. In another recent study, a positive relationship between teachers' reflective practices and their selfregulation was discovered (Pazhoman & Sarkhosh, 2019).…”
Section: Self-regulationmentioning
confidence: 96%